Development of mathematical models to predict the density and hardness of Fe-ZrO2 composites. Issue 3 (3rd July 2022) - Jha, Pushkar; Kumar, Devendra; Mishra, Vijay Kumar
ABSTRACT: Presently, Fe-based metal matrix composites are finding widespread applications in automobile, aviation and railway sectors. Powder metallurgy is one of the preferred techniques to develop these metal matrix composites. In this paper, an attempt has been made to develop the mathematical models to predict the density and hardness of Fe-ZrO2 metal matrix composites, fabricated by powder metallurgy. The experiments were performed on the plan of response surface methodology (RSM)-based Box–Behnken design. The three process parameters considered for this investigation were: sintering temperature (900–1100°C), weight percentages (10–30) of ZrO2, and sintering time (1–3 h). The responses considered for the analysis were density and hardness. Analysis of variance (ANOVA) was used to analyse the significance of the process parameters on the density and hardness. It was observed from the surface plots that sintering time and weight percentage of ZrO2 and their interaction had a significant influence on the density, whereas the weight percentage of ZrO2 individually affects the hardness. The mathematical models developed for the density and hardness were predicted at 95% confidence level. The optimum conditions for process parameters were determined and some useful conclusions were drawn.